Two-dimensional black phosphorus: physical properties and applications. (March 2019) - Mu, X.; Wang, J.; Sun, M.
Abstract: This review focuses on the structure and properties of two-dimensional black phosphorus (BP). First, the crystal and electronic structures of BP are introduced. Second, the anisotropy properties of BP including the band structure and mechanical, thermal, electric, thermoelectric, optical, optoelectronic, magnetic, and magneto-optic properties are described. Third, the applications of BP based on the aforementioned properties are detailed. This review of the properties and applications of BP can not only promote deeper understanding of the physical structure and properties of BP but also enable the rational design of various devices based on BP's properties.